Alternative electrodes for HTMs and noble-metal-free perovskite solar cells: 2D MXenes electrodes. Issue 59 (23rd October 2019) - Cao, Junmei; Meng, Fanning; Gao, Liguo; Yang, Shuzhang; Yan, Yeling; Wang, Ning; Liu, Anmin; Li, Yanqiang; Ma, Tingli
Abstract : The 2D Mxene material was successfully used as the counter electrode of the perovskite solar cell and achieved power conversion efficiencies of 13.84%. Abstract : The high cost of hole transporting materials (HTMs) and noble metal electrodes limits the application of perovskite solar cells (PSCs). Carbon materials have been commonly utilized for HTMs and noble-metal-free PSCs. In this paper, a more conductive 2D MXene material (Ti3 C2 ), showing a similar energy level to carbon materials, has been used as a back electrode in HTMs and noble-metal-free PSCs for the first time. Seamless interfacial contact between the perovskite layer and Ti3 C2 material was obtained using a simple hot-pressing method. After the adjustment of key parameters, the PSCs based on the Ti3 C2 electrode show more stability and higher power conversion efficiencies (PCE) (13.83%, 27% higher than that (10.87%) of the PSCs based on carbon electrodes) due to the higher conductivity and seamless interfacial contact of the MXene electrode. Our work proposes a promising future application for MXene and also a good electrode candidate for HTM and the noble-metal-free PSCs.